Assessing Railway Landscape by AHP Process with GIS: A Study of the Yunnan-Vietnam Railway - Kun Sang; Giovanni Luigi Fontana; Silvia Elena Piovan (Remote Sensing, 2022)
Landscape quality is a crucial factor for the heritage attractiveness of tourism, allowing tourists to experience both natural and cultural aspects along railway journeys. Moreover, railway landscape is a comprehensive system that defines the landscape observed and perceived by passengers and is characterized by the diversity and continuity of the train’s movement. Yunnan-Vietnam railway (YVR) heritage is the research object of this research, whose area encompasses various landscape types and heritage sites, providing great landscape enjoyment. Currently, the assessment methods specifically for railway landscape have been discussed less than for other landscape types, especially for a series of large linear sites like the YVR. To evaluate the value of railway heritage landscape along the railway, this paper proposes a methodology combining the Analytic Hierarchy Process (AHP), Delphi method, and GIS as an integrated spatial assessment. Creatively, this paper seeks to: (1) discuss the relationship between railway and landscape; (2) build a comprehensive evaluation system for the railway heritage landscape, covering the topics of history, tourism, ecology, heritage, social-culture, and visual quality; (3) quantify the landscape value of the YVR areas. Thus, the results of this research can be useful to future urban planning, development, and policymaking.